Animals and posthumanist discourse in children's literature - Sujinah,; Isnah, Encik Savira; Kharis, M. (Humanities, Arts and Social Sciences Studies, 2024)
Children’s literature is associated with various imaginary, impossible, and real creatures that blur the line between reality and fiction, creating a challenge that prompts us to question the rigid, hegemonic humanist worldview in line with the principles of post human thought. Both children’s literature and posthumanism possess a unique potential to present progressive agendas that blend fantastical possibilities with tangible real-world transformations. This article aims to analyze the role of animal characters in challenging anthropocentrism and traditional humanist viewpoints in children’s literature, and to answer research questions How do animal characters in children’s literature function as a critique of anthropocentrism, going beyond mere anthropomorphic portrayals to challenge societal perceptions and prompt considerations of the potential of other entities? To achieve this objective, the qualitative interpretive method is employed, utilizing the data source "Doctor Panda Cures Mr. Gecko's Tail | Super Panda Rescue Team | Baby Bus Cartoon". The findings reveal the following: First, animal characters serve as a counterpoint to anthropomorphism. This underscores the notion that animal characters are necessary for conveying messages effectively to children. Second, animal characters are portrayed on an equal footing with humans. The portrayal of animals in roles such as rescue teams, welders, drivers, and the like is based on their inherent traits. Finally, animals function as a critique of anthropocentrism. This critique extends beyond the concept of animals merely "thinking and acting" like humans; it pushes us to reconsider animals' roles and to explore the potential of non-human entities. This study bridges children’s literature and posthumanism, contending that children's fiction offers a nuanced contribution to the discourse on the essence of humanity, particularly in the context of human-animal relationships.